2021
DOI: 10.3389/fpsyg.2020.601574
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease Stress Among Italian Healthcare Workers: The Role of Coping Humor

Abstract: The study aimed to understand how coping strategies in general and humor-based coping strategies in particular modulate the perception of pandemic-related stress in a sample of Italian healthcare workers during the coronavirus disease (COVID-19) outbreak in Italy. A total of 625 healthcare workers anonymously and voluntarily completed a 10-min questionnaire, which included psychometrically valid measurements preceded by a set of questions aimed at determining workers’ exposure to COVID-19. The Perceived Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 79 publications
7
48
1
Order By: Relevance
“…As for the association between coping strategies and perceived stress, in both groups, resorting to emotion-focused coping strategies (acceptance, seeking emotional support, humor, positive reframing, religion) was negatively related to perceived stress, whereas the dysfunctional one was positively linked to stress. The first association we identified, according to which emotion-focused coping strategies are linked to lower level of perceived stress, thus functioning as a protective factor against negative psychological outcomes, is consistent with the results of many other studies on the general population during COVID-19 [106], as well as on HCWs before COVID-19 [107][108][109] and during it [110,111]. Similarly, also the second association we identified, according to which, on the contrary, dysfunctional coping strategies (behavioral disengagement, denial, self-blame, self-distraction, substance use) are linked to higher levels of perceived stress, is consistent with the results of many other studies [79,100,110], as well as in line with our expectations.…”
Section: Discussionsupporting
confidence: 89%
“…As for the association between coping strategies and perceived stress, in both groups, resorting to emotion-focused coping strategies (acceptance, seeking emotional support, humor, positive reframing, religion) was negatively related to perceived stress, whereas the dysfunctional one was positively linked to stress. The first association we identified, according to which emotion-focused coping strategies are linked to lower level of perceived stress, thus functioning as a protective factor against negative psychological outcomes, is consistent with the results of many other studies on the general population during COVID-19 [106], as well as on HCWs before COVID-19 [107][108][109] and during it [110,111]. Similarly, also the second association we identified, according to which, on the contrary, dysfunctional coping strategies (behavioral disengagement, denial, self-blame, self-distraction, substance use) are linked to higher levels of perceived stress, is consistent with the results of many other studies [79,100,110], as well as in line with our expectations.…”
Section: Discussionsupporting
confidence: 89%
“…While multiple studies have reported on the psychological well-being of healthcare workers during COVID-19 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], our study is one of the first to examine the influence of the pandemic by controlling for before the pandemic in nursing students in Saudi Arabia. Data collection occurred during the first wave of the pandemic in the country.…”
Section: Discussionmentioning
confidence: 99%
“…This was shown in a qualitative study in which nurses in training used humor as a coping strategy to cope with stressful personenvironment relations (e.g., dealing with patients who violate social norms) and to achieve positive affect as an outcome (61). Even in extraordinary times such as the COVID-19 pandemic, humor has been shown to be an effective coping strategy (62) and this was also found for nurses (63,64). People with a greater sense of humor can manage stress more effectively (16).…”
Section: Perceived Stressmentioning
confidence: 89%